Assessment Of Lightweight Recycled Crumb Rubber-Cement Composite Produced By Preplaced Method - Mo, Kim Hung; Othman, Muhammad Nur; Putra, Azma; Shah, Syed Nasir; Yap, Soon Poh (Techno-Press, 2021)
The incorporation of non-biodegradable tyre waste in cement-based material has gained more interest towards sustainable construction these days. Crumb rubber (CR) from waste tyre is an alternative for sand replacement in low strength applications. Many researchers have studied CR cement-based materials produced by normal mixing (NM) method and reported a significant decrease in compressive strength due to CR. To compensate this strength loss, this research aims to study the innovative incorporation of CR in cement composite via the preplaced mixing (PM) method. In this investigation, cement composite was produced with NM and PM methods by replacing sand with 0%, 50%, and 100% CR by volume. The test results showed no significant difference in terms of densities of cement composite prepared with both mixing methods. However, cement composite prepared with PM method had lower strength reduction (about 10%) and lowered drying shrinkage (about 20%). In addition, the sound absorption coefficient and noise reduction coefficient of CR cement composite prepared by PM method were in similar range as those prepared with NM method. Overall, the results demonstrate that the PM method is promising, and the maximum replacement level of 50% is recommended for CR in the cement composite